Does network topology and structure affect the contagion effect of a collapse of a financial institution in an interbank market? A case study on the Barabási–Albert model, Watts-Strogatz model and Erdős–Rényi model - Chew, Wei Jian (Nanyang Technological University, 2021)
This report takes inspiration from the 1998 Asian Financial Crisis, and the resulting cascade of insolvencies of banks in Thailand and Russia in the aftermath. We analysed the contagion effect a collapse of a financial institution would have on other financial institutions in an interbank market. Due to the vast difficulties in acquiring real-world data, a theoretical simulation-based approach was favoured.